Exploring the lead-free halide Cs2MGaBr6 (M = Li, Na) double perovskites for sustainable energy applications - Sofi, Mudasir Younis; Khan, Mohd Shahid; Ali, Javid; Khan, M. Ajmal (Scientific reports, 2024)
In recent years, there has been a growing emphasis on the exploration of sustainable and eco-friendly materials well-suited for advanced applications in the realms of thermoelectrics and optoelectronics. Lead-free halide double perovskites have emerged as a compelling class of materials in this context. Nevertheless, despite their potential utility, thorough investigations into their thermal transport characteristics remain limited. In this systematic investigation, we employ density functional theory (DFT) and post-DFT techniques to elucidate the essential stability parameters, transport properties, and carrier-lattice interactions of the metal halide-based Cs 2 MGaBr 6 (X = Li, Ga) double perovskites. Our assessment of structural stability involves a meticulous description of stability index parameters and the optimization of pristine structures using the GGA-PBE potential. Additionally, we calibrate the electronic structure while taking spin–orbit coupling (SOC) effects into consideration by using a combination of GGA and GGA + mBJ potentials. Our findings reveal that the TB-mBJ derived band gaps of 1.82 eV and 1.78 eV for Cs 2 LiGaBr 6 and Cs 2 NaGaBr 6 reside within the visible spectrum, prompting further investigation into their thermal transport characteristics. Moreover, we analyze the phonon characteristics and vibrational modes, extending our investigation to examine the electron–phonon coupling strength. The scrutiny of the Fröhlich coupling constant and the Feynman polaron radius unveils a stronger electron–phonon coupling strength. In the domain of thermoelectrics, the significant figure of merit (zT) values of 1.08 and 1.04 for Cs 2 LiGaBr 6 and Cs 2 NaGaBr 6 , respectively, emphasize the considerable potential of these materials for deployment in renewable energy applications. Furthermore, our computational investigation into optical properties, including the dielectric constant, optical absorption, and refractive index, demonstrates optimal performance within the visible spectrum. Specifically, elevated absorption coefficient values of 30 × 10 4 cm - 1 for Cs 2 LiGaBr 6 and 40 × 10 4 cm - 1 for Cs 2 NaGaBr 6 are noted across visible and infrared spectra, highlighting their promising potential in optoelectronic and solar cell technologies.